Experimental and numerical analysis of circular concrete-filled double steel tubular stub columns with inner square hollow section. (15th January 2021) - Ci, Junchang; Jia, Hong; Ahmed, Mizan; Chen, Shicai; Zhou, Daxing; Hou, Liqun
Highlights: Axial compression tests on circular CFDST stub columns are carried out. FE model is developed using ABAQUS. Extensive parameter study is performed. Design equation is proposed for calculating the ultimate strengths. Abstract: A circular concrete-filled double steel tubular column (CFDST) with a square hollow section (SHS) as an inner tube is introduced as a new form of a composite column in the paper. A series of axial compression tests that are carried out on this new type of composite column is reported in this study. Three-dimensional models based on the finite element (FE) program ABAQUS are also developed for such columns employing a modified confined concrete constitutive model for the core concrete. The accuracy of the model is verified by comparing the FE model with the experimental results. The effects of various parameters on the load-axial strain response of CFDST short columns are studied by using the validated FE model. The suggested formulas based on the confined concrete model for calculating the bearing capacity of CFDST short columns are proposed.